Image of Minangkabau Women in the Kaba Siti Risani - Chintia, Chintia; Nursaid, Nursaid; Suhaili, Samsudin; Ningsih, Ayu Gustia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to explore: (1) The physical and psychological representation of Minangkabau women in the kaba